Red lesions: autoimmune and malignant conditions - Sciubba, James J. (Henry Stewart Talks, 2017)
Autoimmune conditions, Lichen planus-atrophic, Lichenoid mucositis, Lupus erythematosus, Mucosal pemphigoid, Pemphigus vulgaris, Mucosal-premalignant/malignant lesions, Erythroplakia/Oral epithelial dysplasia, Speckled leukoplakia, Squamous cell carcinoma